Portrait photograph of an unidentified man (Cambridgeport, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Warren (photographer):::Photographer:::::::::::: (Warren; Cambridgeport, MA; United States, 2023)
Portrait photograph of an unidentified man (undated) by Warren, Post Office Block, Cambridgeport, MA from the personal collection of Alexander Wheelock Thayer.